BOWN CORPS AND FIRST GENERATION BRITISH CORPS: COMPARING THEM - Otajonov Sunnatillo Baxtiyorovich (Лучшие интеллектуальные исследования, 2024)
Annotation: To learn and analyze the English language linguistically, one must thoroughly examine and analyze English corpora. Similar language corpora, such as Brown's, were familiar with all the features of language, including some of the innovations and scientific research in its study. Details regarding the construction of the first and second generations' buildings are given.